2012
DOI: 10.1155/2012/429718
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traditional Cupping on Pain and Mechanical Thresholds in Patients with Chronic Nonspecific Neck Pain: A Randomised Controlled Pilot Study

Abstract: Introduction. Cupping has been used since antiquity in the treatment of pain conditions. In this pilot study, we investigated the effect of traditional cupping therapy on chronic nonspecific neck pain (CNP) and mechanical sensory thresholds. Methods. Fifty CNP patients were randomly assigned to treatment (TG, n = 25) or waiting list control group (WL, n = 25). TG received a single cupping treatment. Pain at rest (PR), pain related to movement (PM), quality of life (SF-36), Neck Disability Index (NDI), mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 54 publications
4
108
0
6
Order By: Relevance
“…A trial at the University of Essen studied the effect of dry traditional as well as pulsatile dry cupping in chronic neck pain. Statistically significant and clinically relevant effects of cupping compared to waiting-list control were found after 5 sessions of dry cupping with both methods [10,11], but also an effect of traditional cupping on pain and quality of life already after one cupping session has been observed in this trial [12]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A trial at the University of Essen studied the effect of dry traditional as well as pulsatile dry cupping in chronic neck pain. Statistically significant and clinically relevant effects of cupping compared to waiting-list control were found after 5 sessions of dry cupping with both methods [10,11], but also an effect of traditional cupping on pain and quality of life already after one cupping session has been observed in this trial [12]. …”
Section: Discussionmentioning
confidence: 95%
“…However, recent clinical studies have reported positive results of cupping in patients with musculoskeletal diseases e.g. lower back pain [6], carpal tunnel syndrome [7], brachialgia paresthetica nocturna [8], cancer pain [9] and chronic neck pain [10-12]. In China Cupping is widely used and two systematic reviews were recently published about the results [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We allowed freedom for the selection of points and stimulation methods (wet or dry cupping) to reflect the real-world clinical situation. As it is a very difficult to separate individual factors affecting the specific effects of cupping, most clinical research does not adopt strict standardized treatment guidelines for the cupping procedure, including the size of cups, applied areas, volume of drained air, and retention time of cups 15,30,31,37) . To resolve this problem, two kinds of efforts should be made in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In older days, cups made of bamboo, bone, horn, clay or metal were in use [1]. Many studies have been done to evaluate the efficacy of cupping therapy or hijama in various disorders such as low back pain [2], migraine headache [3], neck pain [4], results show that Hijama has been effective in reducing severity of symptoms without any serious adverse effects.…”
Section: Introductionmentioning
confidence: 99%